Regulation of Bile Acid Synthesis by Fat-soluble Vitamins A and D - Schmidt, Daniel R. (American Society for Biochemistry and Molecular Biology, 2010)
Bile acids are required for proper absorption of dietary lipids, including fat-soluble vitamins. Here, we show that the dietary vitamins A and D inhibit bile acid synthesis by repressing hepatic expression of the rate-limiting enzyme CYP7A1. Receptors for vitamin A and D induced expression of Fgf15, an intestine-derived hormone that acts on liver to inhibit Cyp7a1. These effects were mediated through distinct cis-acting response elements in the promoter and intron of Fgf15. Interestingly, transactivation of both response elements appears to be required to maintain basal Fgf15 expression levels in vivo. Furthermore, whereas induction of Fgf15 by vitamin D is mediated through its receptor, the induction of Fgf15 by vitamin A is mediated through the retinoid X receptor/farnesoid X receptor heterodimer and is independent of bile acids, suggesting that this heterodimer functions as a distinct dietary vitamin A sensor. Notably, vitamin A treatment reversed the effects of the bile acid sequestrant cholestyramine on Fgf15, Shp, and Cyp7a1 expression, suggesting a potential therapeutic benefit of vitamin A under conditions of bile acid malabsorption. These results reveal an unexpected link between the intake of fat-soluble vitamins A and D and bile acid metabolism, which may have evolved as a means for these dietary vitamins to regulate their own absorption.